1995
DOI: 10.1055/s-0038-1649949
|View full text |Cite
|
Sign up to set email alerts
|

Absence of In Vitro Cross-Reaction of Pentasaccharide with the Plasma Heparin-Dependent Factor of Twenty-Five Patients with Heparin-Associated Thrombocytopenia

Abstract: mbH (Stuttgart) 74 (5) 1379-87 (1995) investigators suggested that coagulometer effects on INR may be corrected by using lyophilized plasma calibrants (7). Most authors agree that calibration of APTT methods should be per formed with ex vivo heparin samples, i.e. plasma samples from patients treated with heparin (2, 3, 4). It is not known whether lyophilized samples from heparin-treated patients can replace fresh samples for reliable calibration of APTT methods. The spread of individual patients' samples about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 1 publication
1
30
0
1
Order By: Relevance
“…1 The inability of fondaparinux to induce platelet activation in the presence of HIT sera was demonstrated in previous smaller studies. 14,15 We confirm this finding over a large range of fondaparinux concentrations using 3 complementary qualitative assays. Furthermore, using flow cytometry, we show that the addition of fondaparinux to HIT sera and platelets did not result in platelet activation as measured using annexin V, activation of GpIIb-IIIa, or the release of dense granules.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…1 The inability of fondaparinux to induce platelet activation in the presence of HIT sera was demonstrated in previous smaller studies. 14,15 We confirm this finding over a large range of fondaparinux concentrations using 3 complementary qualitative assays. Furthermore, using flow cytometry, we show that the addition of fondaparinux to HIT sera and platelets did not result in platelet activation as measured using annexin V, activation of GpIIb-IIIa, or the release of dense granules.…”
Section: Discussionsupporting
confidence: 73%
“…This result is consistent with the fact that, in vitro, fondaparinux did not cross-react with HIT-associated antibodies. [14][15][16][17] However, these in vitro studies, using a limited set of sera and different methodologies of variable sensitivity and specificity, did not permit a definitive conclusion to be made regarding the safety of fondaparinux in terms of its ability to induce platelet activation in the presence of HIT-associated antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Further, previous studies have shown that serum obtained from patients with HIT contain anti-PF4/heparin antibodies that consistently fail to react against PF4 in the presence of fondaparinux. 34,35 For these reasons, it seemed probable that fondaparinux would not be associated with antibody formation, or at least would show a significantly lower frequency of antibody formation than LMWH.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike these other molecules, our studies show fondaparinux is unique in that although its administration can be associated with formation of anti-PF4/heparin antibodies that are indistinguishable from those generated during LMWH therapy, these antibodies do not bind well to PF4/fondaparinux, at least under the physicochemical conditions we used. Presumably, the antigens must be expressed on PF4 in the presence of fondaparinux (so as to effect immunization) despite the difficulty in demonstrating this binding in vitro by ourselves (using the fluid-phase EIA) and others (using solid-phase EIA 34,35 and platelet activation assays 35 ). However, evidence that fondaparinux does interact with PF4 in a way that influences antigen expression is suggested by our observation that very high (suprapharmacologic) concentrations of fondaparinux inhibit binding of anti-PF4/polysaccharide antibodies within HIT sera in both solid-phase and fluid-phase EIAs (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Small studies have shown no cross-reactivity of fondaparinux with sera from patients with heparin-induced thrombocytopenia. [37][38][39] Because they are too short to bridge antithrombin to thrombin, fondaparinux and idraparinux enhance the rate of factor Xa inactivation by antithrombin, thereby blocking thrombin generation, but have no effect on the rate of thrombin inhibition. Both agents have almost complete bioavailability after subcutaneous injection.…”
Section: Indirect Factor Xa Inhibitorsmentioning
confidence: 99%